2002
DOI: 10.1164/ajrccm.165.4.2011118
|View full text |Cite
|
Sign up to set email alerts
|

Intratracheal Endotoxin Causes Systemic Inflammation in Ventilated Preterm Lambs

Abstract: Intratracheal endotoxin causes acute inflammation in the adult lung, and injurious styles of mechanical ventilation can result in systemic inflammation derived from the lungs. We asked how ventilated premature and near-term lungs responded to intratracheal endotoxin and if systemic inflammation occurred. Lambs delivered at 130 d gestational age (GA) were treated with surfactant or surfactant plus endotoxin (0.1 mg/kg or 10 mg/kg) (Escherichia coli, serotype O55:B5) and were ventilated for 6 h. Both endotoxin d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
41
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 39 publications
4
41
1
Order By: Relevance
“…We previously reported increased lung mRNA expression of these cytokines by 2h in ventilated preterm lambs compared with unventilated fetal controls (11). In addition, we demonstrated that exposure to ventilation and IT endotoxin causes a modest increase in lung IL-1␤ and IL-6 mRNAs in preterm and near term lambs (23-and 13-fold respectively) (14). We now show a much more robust expression of SAA3 mRNA in the lungs of these animals (366 fold increase).…”
Section: Serum Amyloid A3 Induction In Preterm Lambssupporting
confidence: 57%
See 1 more Smart Citation
“…We previously reported increased lung mRNA expression of these cytokines by 2h in ventilated preterm lambs compared with unventilated fetal controls (11). In addition, we demonstrated that exposure to ventilation and IT endotoxin causes a modest increase in lung IL-1␤ and IL-6 mRNAs in preterm and near term lambs (23-and 13-fold respectively) (14). We now show a much more robust expression of SAA3 mRNA in the lungs of these animals (366 fold increase).…”
Section: Serum Amyloid A3 Induction In Preterm Lambssupporting
confidence: 57%
“…Mechanical ventilation contributes to neonatal morbidity and mortality (9,10) by causing lung inflammation with the induction of the proinflammatory cytokine cascade (11)(12)(13). Intratracheal endotoxin induces both lung inflammation and a systemic inflammatory response in preterm and term ventilated lambs (14). Whether there is induction of a lung acute phase reactant response in these models is not known.…”
mentioning
confidence: 99%
“…However, inflammation must be controlled to avoid systemic inflammation, which may be lethal. 54,70 Many factors affect the modulation of the inflammatory response, such as antenatal steroid therapy, resuscitation, surfactant therapy, mechanical ventilation, oxygen toxicity and pulmonary and/or systemic infection. 7 Along with the immaturity of the preterm immune system, 71 antenatal and postnatal factors may also condition and modulate the pulmonary inflammation.…”
Section: Glucocorticoids and Chorioamnionitismentioning
confidence: 99%
“…Termventilated lambs do not leak endotoxin from the airspaces into the systemic circulation unless the lungs are over-stretched (16). In contrast, preterm lungs leak endotoxin or IL-1 with conventional ventilation (16,17).…”
mentioning
confidence: 99%
“…Termventilated lambs do not leak endotoxin from the airspaces into the systemic circulation unless the lungs are over-stretched (16). In contrast, preterm lungs leak endotoxin or IL-1 with conventional ventilation (16,17). Chorioamnionitis is associated with many preterm deliveries before 32 wk gestational age, and inflammatory mediators are present in the fetal lung (18,19).…”
mentioning
confidence: 99%